2008
DOI: 10.1007/bf03346407
|View full text |Cite
|
Sign up to set email alerts
|

Screening of follicle-stimulating hormone receptor gene in women with premature ovarian failure in southern Brazil and associations with phenotype

Abstract: We investigated the presence of mutations/polymorphisms in the FSH receptor (FSHR) gene and their association with phenotype in women with premature ovarian failure (POF) in southern Brazil. Clinical and hormonal variables were determined in 36 46,XX women with primary or secondary amenorrhea before the age of 40 yr, FSH >40 IU/l and ovarian failure. DNA was isolated from peripheral leukocytes. Exons 6, 7, 9, and 10 of the FSHR gene were analyzed by PCR, restriction enzyme analysis, denaturing gradient gel ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…As shown in Table 1, mutations reported in exons 7 and 10 are always associated with primordial follicles (PFs) up to pre-antral stage. A large number of studies have been undertaken to search for mutations in FSHR in women having POF or ROS with negative results in New Zealand (Woad et al 2013), India (Achrekar et al 2010), Argentina (Sundblad et al 2004), Japan (Takakura et al 2001), Mexico (de la Chesnaye et al 2001), the UK (Conway et al 1999), and Brazil (Vilodre et al 2008). First, reported Finnish mutation in FSHR by Aittomaki et al (1995) was not found in 35 American women with ovarian failure (Layman et al 1998) and was found in only one woman out of a total of 2840 women screened from Switzerland, Denmark, and Singapore (Jiang et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, mutations reported in exons 7 and 10 are always associated with primordial follicles (PFs) up to pre-antral stage. A large number of studies have been undertaken to search for mutations in FSHR in women having POF or ROS with negative results in New Zealand (Woad et al 2013), India (Achrekar et al 2010), Argentina (Sundblad et al 2004), Japan (Takakura et al 2001), Mexico (de la Chesnaye et al 2001), the UK (Conway et al 1999), and Brazil (Vilodre et al 2008). First, reported Finnish mutation in FSHR by Aittomaki et al (1995) was not found in 35 American women with ovarian failure (Layman et al 1998) and was found in only one woman out of a total of 2840 women screened from Switzerland, Denmark, and Singapore (Jiang et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This controlled cross-sectional study included 32 patients with POI consulting at the Gynecological Endocrinology Unit of Hospital de Clínicas de Porto Alegre, Brazil, since March 1999 (12). Women with primary or secondary amenorrhea before the age of 40 years, a normal 46XX karyotype and FSH levels higher than 40 IU/L in at least two consecutive measurements were selected.…”
Section: Patients and Reference Groupsmentioning
confidence: 99%
“…POI is a fairly common condition, affecting approximately 1 in 10,000 women by age 20, 1 in 1000 women by age 30, and 1 in 100 women by age 40 (1). The causes of POI are heterogeneous (2,3). Most cases are idiopathic, but acquired forms may occur after treatment for neoplastic or autoimmune diseases (3).…”
mentioning
confidence: 99%
“…Essa variabilidade da evolução clínica foi também observada numa coorte de 39 pacientes com FOP e cariótipo 46 XX, que estão sendo acompanhadas na Unidade de Endocrinologia Ginecológica do Serviço de Endocrinologia, no Hospital de Clínicas de Porto Alegre. Verificou-se nestas pacientes que a idade mediana da última menstruação variou de 14 a 39 anos, e que a duração da irregularidade menstrual antes do diagnóstico firmado de FOP foi inferior a 3 anos em 44% da amostra e superior a 9 anos em 16% das pacientes (8).…”
Section: Definição Prevalência E Apresentação Clínicaunclassified
“…Entretanto, freqüentemente o diagnóstico é retardado pela demora na avaliação diagnóstica destas pacientes. As pacientes com FOP e amenorréia secundária apresentam, em geral, menarca na idade habitual, ciclos inicialmente regulares e que, a partir de um determinado período, tornam-se irregulares variando de oligomenorréia a períodos de amenorréia, até a cessação completa das menstruações (7,8). Inicialmente, e dependendo do grau de comprometimento ovariano, podem ser mais evidentes os sintomas vasomotores, como fogachos e sudorese, alteração de humor e insônia, evoluindo mais tardiamente para a atrofia do trato urogenital, com maior propensão para vaginites, cistites e dispareunia.…”
Section: Diagnósticounclassified